KEBIJAKAN PEMERINTAH THAILAND DALAM MENANGGULANGI PARIWISATA SEX TAHUN 2014-2018 - Dina Octavia; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Tourism sector is one of priority sector in Thailand that supports the biggest income of this country. But, the massive tourism development in Thailand also has tight relation by increasing the prostitution level. Sex tourism becomes one of phenomenon that brings it to the dilemma position. Although it becomes the income source for Thailand, but the negative impact occurs such as HIV/AIDS, human trafficking, and bad image of Thailand. Those things makes Thailand’s government implement the work program of image re-branding of tourism sector. The method used in this research is qualitative descriptive. This research uses secondary data by using library research. This study uses Postmodernism Perspective Level of Interest Group, and Theory of Constructivism. The result of this research is Thailand has implemented various ways of public diplomacy effort to pay attention of tourist so that they forget Thailand’s image as sex tourism country. From various ways that have been done by Thailand, it has not lost the negative image of Thailand from international perspective, but Thailand has obtained various international awards in tourism sector that becomes representation of its achievement. Keywords: Sex Tourism, Thailand, International Tourism